Thermal Life of Carbon Structures: From the Earth to after the Titan - A. Anvari (International Journal of Aerospace Engineering)
With the increasing of consumption of sources and the population of mankind on Earth, scientists are looking for an alternative planet in the solar system that can establish the second home for mankind. Previously, Mars has been the center of attention by scientists due to the closer distance to Earth and being similar to that in many aspects. Recently, scientists discovered that there may be a better alternative. Titan, despite its great distance from the Earth, seems like a better planet for the mankind colonization due to its atmosphere that create a shield against the radiation in comparison to Mars’ atmosphere that is thin and is not capable to create an adequate shield against radiation. In the previous work, the thermal life of carbon structures on Mars was approximately estimated. The aim of this research is to provide a method to estimate the thermal life of carbon structures on Titan. Carbon structures are currently used in space structures due to their lightweight and strength.